Concept Understanding Students on the Two-Variables Linear Equation System Material in Terms of Mathematics Ability - Rahmadiani Rahmadiani; Alfisyahra Alfisyahra; Rita Lefrida; Pathuddin Pathuddin (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
The purpose of this study was to describe the concept understanding ability of students in solving the problem of two-variable linear equation system. The method used is descriptive qualitative research. The subject of this research was 3 students taken from 26 students of class VIII SMPN 1 Balaesang. The results showed that the concept understanding of high mathematics ability students in restating concepts can restate concepts well using their own language, identify examples and non-examples and classify objects according to certain properties in accordance with the concept that can make mathematical modelling and determine equations and use the right solution steps according to the concept algorithmically. The concept understanding of medium ability students in restating concepts has been able to state concepts using their own sentences, identify examples and non-examples and are still lacking in classifying objects according to certain properties in accordance with the concept. The concept understanding of low ability students has not been able to achieve all indicators of concept understanding. Therefore, concept understanding is very important to be mastered by every student and the role of the teacher in facilitating the ability of each student.